Tomato leaf curl Patna virus causing tomato leaf curl disease in Bangladesh - Islam, Mohammad Nurul; Ansari, Aneesa; Sarker, RH (Bangladesh Journal of Botany, 2019)
Tomato leaf curl virus (ToLCV) has appeared as a potential threat to the tomato production in the world. ToLCV, a member of the family Geminiviridae may contain either bipartite or monopartite genome. The genetic nature of a monopartite ToLCV isolate characterized from the tomato leaf curl diseased samples of Jamalpur district, Bangladesh (ToLCV-JB) has been reported. The products of rolling circle amplification (RCA) were digested, cloned and sequenced. Sequence analysis revealed the features of begomovirus genome organization in the ToLCV-JB isolate, containing six open reading frames. BLAST analysis showed 100% sequence similarity with tomato leaf curl Patna virus (EU862323.1) and more than 80% similarity with other reported monopartite begomoviruses. Hence, the virus isolate was registered as Tomato leaf Curl Patna virus-[Bangladesh:Jamalpur:2014] isolate ToLCV-JB (Genebank Accession: KU933675.1) according to the suggestion of NCBI. Recombination analysis also did not show any genetic exchange between ToLCV-JB and ToLCV-Patna virus. Moreover, they belong to the same cluster as observed in phylogenetic analysis. The present work suggests the possibility of cross-border spread of ToLCV-Patna viruses without mutation and this could pose a threat to tomato production in Bangladesh as well as in the Asian continent.